Cuproptosis-related gene ACAD8 inhibits the metastatic ability of colorectal cancer by inducing cuproptosis - Zhuang, HuiE; Chen, Yizhen; Huang, Sifu (Frontiers in Immunology, 2025)
BackgroundDistant metastasis of colorectal cancer (CRC) significantly impacts patient prognosis. Cuproptosis is a new form of copper ion-dependent cell death. However, whether cuproptosis-related genes (CRGs) play a role in the metastatic potential of CRC remains unclear. This study focuses on CRGs-ACAD8 to explore its role and mechanism in metastatic CRC (mCRC).MethodsClinical sample data from TCGA, GEO, and Fujian Provincial Hospital patients were integrated to analyze ACAD8 expression and its association with the diagnosis and prognosis of CRC. Small interfering RNA, immunohistochemistry, colony formation, wound-healing assays and so on were used to evaluate the biological functions of ACAD8. Bioinformatics was applied to investigate its relationships with immune infiltration, chemotherapy sensitivity, and signaling pathways.ResultsACAD8 expression was significantly reduced in mCRC and demonstrated excellent diagnostic performance. Patients with high ACAD8 expression had significantly better survival. ACAD8 was closely associated with immune cell infiltration, and enhanced chemotherapy sensitivity. Pathway enrichment analysis suggested that ACAD8 might inhibit the metastasis of CRC by regulating pathways such as response to metal ions and tight junction organization. Finally, experiments confirmed a positive correlation between copper levels and ACAD8 mRNA expression, with CuCl2 upregulating ACAD8 expression. Knockdown of ACAD8 induced cuproptosis. CuCl2 inhibited the proliferation, stemness, and migratory abilities of CRC cells, while si ACAD8 attenuated these effects. Moreover, CuCl2 enhanced the sensitivity of CRC cells to oxaliplatin and 5-fluorouracil, whereas si ACAD8 diminished this chemosensitizing effect.ConclusionAs a novel tumor suppressor, low expression of CRGs-ACAD8 is associated with the metastasis of CRC. ACAD8 holds potential diagnostic and prognostic value and may contribute to the precise treatment of CRC by regulating immune infiltration and chemotherapy sensitivity.